Effect of heterocycles on field-effect transistor performances of donor-acceptor-donor type small molecules - Chini, Mrinmoy Kumar; Mahale, Rajashree Y.; Chatterjee, Shyambo (Chemical Physics Letters, 2016)
Two D-A-D small molecules comprising triphenylamine and diketopyrrolopyrrole were synthesized having either furan or thiophene connected to the fused lactam ring. In this design, furan/thiophene diketopyrrolopyrrole acts as an acceptor and triphenylamine acts as a donor. Propeller shaped triphenylamine has its effect on packing, processability and plays a vital role in determining the pi-pi molecular orbital stacking in such compounds and thus the mobility of charge carriers. With TDPPT and FDPPT, maximum hole carrier mobility obtained is 2.88 x 10(-3) cm(2) V-1 s(-1) and 1.60 x 10(-3) cm(2) V-1 s(-1), respectively using bottom gate bottom contact field-effect transistor. (C) 2016 Elsevier B.V. All rights reserved.

F and CF3 substituted solution processable oligo para-phenylenevinylene for ambipolar and hole-transporting organic field effect transistors - Chini, Mrinmoy Kumar; Das, Chayanika; Chatterjee, Shyambo (Chemical Physics Letters, 2016)
We have synthesized benzotrifluoromethyl group substituted para-phenylenevinylene oligomer (denoted as PI) and a cooligomer (denoted as PII) by Gilch polymerization route. The ambipolar field-effect transistor (FET) material PI shows hole and electron mobility 1 x 10 (4) cm(2) V (1) s (1) and 2 x 10 (5) cm(2) V (1) s (1) respectively. PII shows only hole mobility as high as 0.05 cm(2) V (1) s (1) as p-type material. This work highlights the progress of hole-transporting as well as ambipolar material for para-phenylenevinylene derivatives. The results are enlightened on the basis of presence of electronegative substituents and structural modification of the oligomer backbone. (C) 2016 Elsevier B.V. All rights reserved.

Effect of side-chain functionality on the organic field-effect transistor performance of oligo(p-phenylenevinylene) derivatives - Chini, Mrinmoy Kumar; Chatterjee, Shyambo (Journal of Applied Polymer Science, 2017)
In order to observe the effects of the substitution of electronegative flourine with aromatic groups in oligo(p-phenylenevinylene) compounds on their packing, morphology, and charge carrier mobility, we have synthesized napthol-substituted oligo(p-phenylenevinylene) compounds and examined their solubility, redox properties, thin film morphologies, and charge carrier properties. To date, very few examples of conjugated oligomers bearing napthol side groups have been reported in the literature. After annealing at 150 degrees C, the mobility of S1, S2, and S3 was 4.0x10(-2) cm(2) V-1 s(-1), 1.2x10(-2) cm(2) V-1 s(-1), and 2.6x10(-3) cm(2) V-1 s(-1), respectively. (c) 2017 Wiley Periodicals, Inc.

Hydrothermally reduced nano porous graphene–polyaniline nanofiber composites for supercapacitor - Chini, Mrinmoy Kumar; Chatterjee, Shyambo (FlatChem, 2017)
Hydrothermally reduced porous graphene (PGs) and polyaniline (PANI) nanofiber composites (PGs?PANI) were prepared by interfacial polymerization of aniline in the presence of reduced porous graphene (PGs) under acidic conditions. Hydrothermal reduction of graphene oxide (GO) produced graphene quantum dots (GQDs) along with porous reduced graphene (PGs). The removal of nano sized GQDs generate several round shaped edges in the graphene, which facilitated improved charge storage. In addition to preparation of porous graphene, we developed an approach to process the PGs. We envisioned preparing conjugated polymer as processing material. The capacitive behavior of PGs was characterized using cyclic voltammetry (CV) and galvanostatic charge?discharge (GCD) techniques. The specific capacitance of hydrothermally reduced GO (PGs) and PGs?PANI composites was 185 F/g and 357 F/g at 0.1 A/g in 1 M H2SO4 electrolyte. The energy density of PGs?PANI composite was obtained 49.58 W h/kg at a power density of 71.8 W/kg.

Influence of thermocleavable functionality on organic field-effect transistor performance of small molecules - Mahale, Rajashree Y.; Dharmapurikar, Satej S.; Chini, Mrinmoy Kumar; Venugopalan, Vijay (Chemical Physics Letters, 2017)
Diketopyrrolopyrrole based donor-acceptor-donor conjugated small molecules using ethylene dioxythiophene as a donor was synthesized. Electron deficient diketopyrrolopyrrole unit was substituted with thermocleavable (tert-butyl acetate) side chains. The thermal treatment of the molecules at 160 degrees C eliminated the tert-butyl ester group results in the formation of corresponding acid. Optical and theoretical studies revealed that the molecules adopted a change in molecular arrangement after thermolysis. The conjugated small molecules possessed p-channel charge transport characteristics in organic field effect transistors. The charge carrier mobility was increased after thermolysis of tert-butyl ester group to 5.07 x 10(-5) cm(2)/Vs. (C) 2017 Elsevier B.V. All rights reserved.

Synthesis of amphiphilic isoindigo co-polymers for organic field effect transistors: A comparative study - Dharmapurikar, Satej S.; Arulkashmir, Arulraj; Mahale, Rajashree Y.; Chini, Mrinmoy Kumar (Journal of the apllied polymer science, 2017)
In this work, the amphiphilic isoindigo (am-iInd) based conjugated polymers namely poly(am-iInd-DT) and poly(am-iInd-TT) and their regular counterpart poly(reg-iInd-DT) and poly(reg-iInd-TT) were synthesized to compare their opto-electronic and charge transport properties. They were used to fabricate organic field effect transistors. Charge transport properties in conjugated polymers depend upon intermolecular interaction which is strongly affected by the nature of side chains. The amphiphilic nature of the conjugated polymers has little impact on the charge transport properties. The charge carrier mobility of amphiphilic conjugated polymers was comparable with the regular polymers except poly(reg-iInd-DT) which can be correlated by X-ray diffraction and thin film morphology. (c) 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2017, 134, 45461.
Keywords: Alkyl; Applications; Conducting polymers; Copolymers; Optical and Photovoltaic applications; conjugated polymers; High-performance; mobility; Packaging; Semicondoctors; Side-chains; Solar-cells; Thin-film Transformer

Chemical oxidative and solid state synthesis of low molecular weight polymers for organic field effect transistors - Mahale, Rajashree Y.; Dharmapurikar, Satej S.; Chini, Mrinmoy Kumar (Chemical Physics Letters, 2018)
Solution processability of the precursor molecules is a major issue owing to their limited solubility for the synthesis of conjugated polymers. Therefore, we favour the solvent free solid state chemical oxidative polymerization route for the synthesis of diketopyrrolopyrrole (DPP) based donor-acceptor (D-A) type conjugated polymers. D-A type polymer Poly(S-OD-EDOT) which contains DPP coupled with EDOT donor units is synthesized via solid state polymerization method. The polymer is employed as an active layer for organic field-effect transistors to measure charge transport properties. The Polymer shows good hole mobility 3.1 x 10(-2) cm(2) V-1 s(-1), with a on/off ratio of 1.1 x 10(3). (C) 2018 Elsevier B.V. All rights reserved.

Nanoporous reduced graphene oxide and polymer composites as efficient counter electrodes in dye-sensitized solar cells - Sudhakar, Vediappan; Singh, Anup Kumar; Chini, Mrinmoy Kumar (ACS Applied Electronic Materials, 2020)
The introduction of an efficient and precious platinum (Pt) free counter electrode (CE) for dye-sensitized solar cells (DSSCs) is an important aspect to address. In this report, we have employed nanoporous reduced graphene oxide (PG) containing PEDOT:PSS-PG composite on FTO substrate as CEs, which have shown excellent diffusion of I-3(-), remarkable photocatalytic activity, and better device performance along with desired stability. The investigated cathode material has been prepared by mixing PGs and highly conducting PEDOT:PSS. Experimental measurements and analyses such as electrochemical impedance spectroscopy (EIS), cyclic voltammetry (CV), and so on indicate that PEDOT:PSS-PG is a promising cathode material for a Pt-free CE in DSSCs. EIS indicates that the PEDOT:PSS-PGs have lower interfacial charge-transfer resistance because of their high electrical conductivity and superior electrocatalytic activity. The achieved photoconversion efficiency (eta) of a DSSC employing the Pt-free PEDOT:PSS-PG/FTO CE is 9.57%, which is found to be comparable to that of Pt/FTO CE based DSSC (9.64%) under a simulated solar light illumination of 100 mW/cm(2).
Keywords: counter electrode; Dye-sensitized solar cells; electrocatalytic activity; PEDOT:PSS; Reduced graphene oxide

Significance of secondary forces toward improving the charge carrier mobility of Isoindigo based conjugated small molecules - Dharmapurikar, Satej S.; Kashmir, Arulraj Arul; Kumari, Tanya; Kalalawe, Virbhadra; Kanetkar, Maruti; Chini, Mrinmoy Kumar (Chemical Physics Letters, 2021)
The charge carrier mobility of conjugated small molecules (CSMs) depends on the intermolecular interactions and morphology. Herein, we report the synthesis of CSMs having different side chains. Hydrogen bonding, lipophilic imbalance and van der Waals interactions are imparted through the asymmetric substitution of Isoindigo. The secondary forces impact thin film morphology, and charge carrier mobility. The CSMs having van der Waals interaction further shows higher charge carrier mobility as a function of improved morphology, and increased temperature. The highest mobility of 0.15 cm2/Vs has been achieved for CSMs with van der Waals interaction.
Keywords: Conjugated small molecules; Isoindigo; mobility; OFET; Secondary force